2012
DOI: 10.1002/path.4124
|View full text |Cite
|
Sign up to set email alerts
|

Danger‐associated molecular patterns (DAMPs) in acute lung injury

Abstract: Danger-associated molecular patterns (DAMPs) are host-derived molecules that can function to regulate the activation of pathogen recognition receptors (PRRs). These molecules play a critical role in modulating the lung injury response. DAMPs originate from multiple sources, including injured and dying cells, the extracellular matrix, or exist as immunomodulatory proteins within the airspace and interstitium. DAMPs can function as either toll-like receptor (TLR) agonists or antagonists, and can modulate both TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 135 publications
(147 reference statements)
3
93
0
Order By: Relevance
“…We previously reported that elevated IL-10 and reduced IL-12p70 in bronchial washings were statistically significantly associated with ALI following inhalation injury (14). It has been postulated that DAMPs released from damaged tissues drive immune dysfunction after injury (3,16,27). We therefore hypothesized that increased DAMPs released from damaged tissue would correlate with bacterial infection and IL-10/IL-12p70 levels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously reported that elevated IL-10 and reduced IL-12p70 in bronchial washings were statistically significantly associated with ALI following inhalation injury (14). It has been postulated that DAMPs released from damaged tissues drive immune dysfunction after injury (3,16,27). We therefore hypothesized that increased DAMPs released from damaged tissue would correlate with bacterial infection and IL-10/IL-12p70 levels.…”
Section: Discussionmentioning
confidence: 92%
“…The primary function of TLR is to be "pattern recognition receptors" for the innate immune system, capable of sensing molecules normally associated with microorganisms (1,2). Endogenous ligands also exist for mammalian innate receptors with both necrotic and apoptotic cells able to induce cell signaling through TLR and other innate sensing molecules via release of endogenous ligands, known as DAMPS such as HA, ds-DNA, HSP-70, and HMGB-1 (3,27). We and others have shown that TLR expression and signaling is often altered after injury leading to hypo-or hyper-responsiveness (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several triggering conditions, including hemorrhagic shock, endotoxin, trauma, burn injury, and ischemia–reperfusion, contribute to ALI and exaggerate the inflammatory process of ALI [2325]. NF-κB is an important nuclear transcription factor that upon activation, transfers into the nucleus, amplifying inflammatory responses by promoting production of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-8 [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In our aspiration model, increased expression of RAGE in the lung, upregulated by high dietary AGEs, constitutes the ‘first hit’. The ‘second hit’ comes from the low-pH cellular injury of gastric aspiration, releasing a variety of endogenous danger signals known as damage associated molecular patterns (DAMPs) [11]. …”
Section: Introductionmentioning
confidence: 99%